The Effectiveness of a Mindfulness Training Program on Selected Psychological Indices and Sports Performance of Sub-Elite Squash Athletes - Wong, R. S. K.; How, P. N.; Cheong, J. P. G. (Frontiers in Psychology, 2022)
Mindfulness Acceptance Commitment (MAC) programs have garnered much support in enhancing sport performance through present-moment focus and non-judgmental thoughts. While past research observed the effects of MAC in collegiate and professional settings, the present study expanded current knowledge in this area by utilizing a single case A-B design among national sub-elite athletes to observe changes in proficiency of mindful practice through the Mindfulness Awareness Acceptance Scale (MAAS) and of experiential avoidance through the Acceptance Action Questionnaire (AAQ-II). In addition, stress levels were observed through the Perceived Stress Scale (PSS) and sport performance were monitored through a Coach’s Rating Scale of Athlete’s Performance and an Athletes Performance Self- Rating Scale. A total of six sub-elite Malaysian Squash athletes (2 males, 3 females; Mage = 15 ± 2 years) were purposively sampled from the Malaysian national squash team. Participants underwent six weeks of baseline testing, seven weeks of program intervention, and a retention test four weeks post-intervention. The intervention consisted of psycho-education, centering and cognitive defusion among other aspects as purported in MAC programs. Overall, visual analysis revealed improvements in MAAS levels (M = 1.15 ± 0.15), with no marked changes in AAQ-II (M= -0.002 ± 1.12) and PSS (M = 0.7 ± 0.93) after seven weeks of intervention. Coach-rated sport performance also improved across the phases (M = 0.86 ± 0.93), with mixed responses for self-rated improvements (M = 0.01 ± 1.19). Overall, the benefits of MAC program were well-maintained past the post-intervention phase. The current study supported the implementation of an MAC program for sub-elite athletes in real-world settings.